Digital knowledge mapping in educational contexts - Hanewald, R.; Ifenthaler, Dirk (2014)
This chapter provides an introduction to knowledge mapping for the novice reader. It will start with a brief overview of the historical origins of concept maps and the learning theories that underpin them. It is followed with a discussion on the various definitions of maps by the authors who are postulating their own definition. Additional terminology is presented in the section explaining the anatomy of a knowledge map, while a simple ten-step process guides readers through the creation of their own map. This can either be a concept or a mind map, with the digitally, with a short explanation of the advantages and disadvantages of each approach before launching into a section that provides an indication of various mapping software and their main features. The chapter concludes with a synopsis of the current knowledge base in the research literature on knowledge maps in educational contexts. It will enable familiarisation with the field and provide a foundation for the following chapters containing empirical and theoretical work, which form the remainder of the book.